Aggressiveness of fusarium section liseola isolates causing maize ear rot in Argentina - Iglesias, Juliana (2010)
Developing resistance to species of Fusarium in maize (Zea mays L.) is important to prevent field mycotoxin contamination. Isolates representative of natural conditions need to be identified to maximize selection responses. Sixty isolates belonging to Fusarium section Liseola collected from a major maize growing region in Argentina were tested for sexual compatibility with eight standard tester strains (A-H) of the Gibberella fujikuroi complex. A twenty-nine isolate sub-sample (MAT-A: 26, MAT-E: 2 and MAT-D: 1) was tested for in vitro production of fumonisins and for aggressiveness to two maize hybrids after silk inoculation. Mating population A (F. verticillioides) was the most prevalent species (90%) coexisting with some isolates belonging to MAT-D (F.proliferatum) and MAT-E(F. subglutinans). Fumonisin production varied from 0.4 to 2884 mg g-1 for MAT-A and from 0.3 to 0.6 mg g-1 for MAT-E. The only isolate from MATD produced undetectable levels. Most isolates showed mild aggressiveness but two uncommon highly aggressive strains (MAT-A and D) were also identified. No associations between fumonisin production and disease severity were observed. Differences in disease severity between moderately resistant and susceptible hybrids varied across years and isolates suggesting that responses to selection might depend on the isolate used to produce the inoculum. The use of isolate mixtures might reduce genotype-by-isolate interaction although it would hinder identification of resistance to specific strains.